An analysis non living personification in northlane’s selected songs - Darmarris, Genvil; Putri, IGA Vina Widiadnyana (Journal of Language and Applied Linguistics, 2020)
This article aims to identify which lyrics contain the Non living personification used in the selected songs of metal band, Northlane, and their meaning. The theory used is the theory from Zhu (1991) to identify which lyrics, from selected songs such as: Free fall, Talking Heads, Eclipse, Vultures, contain the Non living personification, and the theory meaning from Leech (1981). The method used in this research is the library method. The method used for presenting data is an informal method, which means that the data will be described qualitatively with description includes several descriptions and support for formal methods. It means that this article used tables to explain the classification of the data used. After analyzing the data, the writer found that in each songs such as : Free fall, Talking Heads, Eclipse, Vultures, there are some lyrics that contain non living personification based from theory of personification by Zhu (1991). However, there are only 5 out of 7 types of meaning based on the theory of meaning by Leech (1981) that found from the data such as Conceptual, Connotative, Social, Affective And Thematic meaning.